Challenges and opportunities for water conservation in irrigated agriculture in South Africa. Issue 3 (27th May 2021) - de Clercq, Willem; de Witt, Marlene; Laker, Giel
Abstract : This review provides a brief overview of problems in irrigated agriculture that have become more evident as a result of climate change. In most irrigated regions in South Africa, the demand for water is exceeding the supply, as surface water resources in most catchments are already fully or over-allocated. In a regional context, water suppliers should strive to optimally manage the quantity and quality of water distributed to farmers, while providing farmers with up-to-date water quantity and quality information for planning and management purposes. Recent prolonged droughts across most of South Africa have forced water users to review the efficiency of their farming systems. At the farm-scale, efficient irrigation is required by means of effective irrigation scheduling and implementation of appropriate irrigation technologies on suitable soils. The importance of soils information and land management is often underestimated, but these are key elements to successful conservation farming. Farmers should measure irrigation volume and demand, as well as irrigation and soil water quality during irrigation. The high cost of infrastructure changes is a major barrier to farmers becoming more efficient, while a lack of storage dams and the way that water is distributed in irrigation schemes also prevent farmers from being more efficient.